Role of Microfinance on Entrepreneurship Capacity Building - Amrit Shahi (Journal of Nepalese Management and Research, 2024)
Microfinance is pivotal for economic growth and entrepreneurship in Nepal, as evidenced by recent financial reports from leading institutions like CBBL, DDBL, and FOWAD have reported substantial profit increases. Theoretical frameworks and policies emphasize microfinance’s role in poverty reduction and economic development. However, research highlights gaps in understanding its impact on entrepreneurship, financial inclusion, and decision-making, especially in marginalized areas. Empirical studies acknowledge microfinance’s positive effect on entrepreneurship and identify challenges such as limited access and low financial literacy. This study employs structured questionnaire surveys with 150 participants and conducts inferential analysis using SPSS 20 to uncover correlations between microfinance interventions and entrepreneurship outcomes. The proposed conceptual framework explores the relationship between microfinance and entrepreneurship, revealing significant correlations with entrepreneur well-being. Regression analysis indicates that while ability awareness training positively impacts entrepreneurship, micro-credit, micro-insurance, and micro-saving may not directly influence entrepreneur well-being. This underscores the intricate dynamics between microfinance and entrepreneurship, necessitating tailored interventions and policies to support micro-entrepreneurs and foster inclusive development. The analysis highlights the importance of ability awareness training and challenging traditional microfinance strategies. Policymakers are urged to prioritize comprehensive support, focusing on skill enhancement programs. Future research should conduct longitudinal studies to understand the long-term impacts of interventions better and inform policy development for more effective practices. By linking theory, empirical evidence, and practical applications, this study offers a comprehensive understanding of how microfinance can be optimized to support entrepreneurship and economic growth in Nepal.